Knowledge for spatial policy: the role of strategic research - WISSERHOF, Johan (European Spatial Research and Policy, 1998)
The direct contribution of research to the preparat i on of spatial poilicy in the Netherlands is relatively small. The policy-making processes rely heavily on the utilisation of 'in-stock' knowledge. The knowledge stock, however, has been built up partly by strategie research. Strategie research, therefore, is an indirect source of knowledge for spatial policy. Strategie research is defined as systematic investigation to acquire knowledge that may contribute to the solution of medium- or long-term societal problems. In this paper, the question is posed how strategic research can be conducted in such a way that it contributes to the knowledge stock for spatial policy. The answer is sought in a multiperspective, interdisciplinary and actor-oriented researeh approach. Such an approach in a way complies with the multiple perspectives of policy-makers on societal problems: Technical, Organisational and Personal/Political (T+O+P). The information needs of policy-makers are not only problem-oriented (the T perspeetive) but also actor-oriented (the O and P perspectives). A conceptual framework for strategic research is presented which includes multiple perspectives on spatial developments. Five perspectives for spatial research are distinguished: the social construction of spatial developments, the institutionalisation of interests, regional restructuring, societal steering by policy-makers, and the performance of policy. Each of these perspectives involves interdisciplinary and actor-oriented research. The conceptual framework is briefly exemplified by applications in the study of rural regions. Finally, the actual contribution of the conceptual framework to the knowledge stock for spatial policy is discussed.